2012
DOI: 10.1080/13803395.2012.667393
|View full text |Cite
|
Sign up to set email alerts
|

The loss of conceptual associations in mild Alzheimer's dementia

Abstract: Changes in semantic memory are a controversial topic in research on cognitive decline in aging. In this study, we analyzed whether the semantic deficits in mild Alzheimer's disease (AD) reflect the information acquisition process, and whether the deficits are related to when the information was initially stored. We hypothesized that in the earlier stages of dementia, the ability to access semantic associative relations reflects the use of these associations during different developmental stages. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…This finding is in line with other previous findings (Di Giacomo, De Federicis, Pistelli, et al, 2012;Passafiume et al, 2012), which showed that the semantic impairment in AD starts with difficulty in using the semantic associative relationships and not with a deficit in naming of the concepts.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This finding is in line with other previous findings (Di Giacomo, De Federicis, Pistelli, et al, 2012;Passafiume et al, 2012), which showed that the semantic impairment in AD starts with difficulty in using the semantic associative relationships and not with a deficit in naming of the concepts.…”
Section: Discussionsupporting
confidence: 83%
“…It seems that the associative relationships elicited by visuoperceptual stimuli support the associative semantic ability when the breakdown of the verbally mediated semantic associative relationships occurs. This hypothesis is coherent with the idea that the deterioration of the semantic network is reverse to the acquisition of the semantic associative relationships in childhood (Di Giacomo, De Federicis, Pistelli, et al, 2012).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Due to the degeneration of semantic networks, AD patients have restricted access to semantic memory content [151–153]. As a consequence, they typically show poor performances in naming tasks that require the identification of objects.…”
Section: Neurocognitive Changes Associated With Alzheimer’s Diseasementioning
confidence: 99%